2007
DOI: 10.1007/s10162-007-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes Across Time in Spike Rate and Spike Amplitude of Auditory Nerve Fibers Stimulated by Electric Pulse Trains

Abstract: We undertook a systematic evaluation of spike rates and spike amplitudes of auditory nerve fiber (ANF) responses to trains of electric current pulses. Measures were obtained from acutely deafened cats to examine time-related changes free from the effects of hair-cell and synaptic adaptation. Such data relate to adaptation that likely occurs in ANFs of cochlear-implant users. A major goal was to determine and compare rate adaptation observed at different pulse rates (primarily 250, 1000, and 5000 pulse/s) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
143
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 87 publications
(162 citation statements)
references
References 42 publications
16
143
3
Order By: Relevance
“…The results of similar experiments by Zhang et al (2007) also showed evidence of reduced excitability due to subthreshold responses although it was not explicitly stated by the authors. True spike rate adaptation should only depend on the onset spike rate.…”
Section: Spike Rate Adaptation and Interacting Phenomenamentioning
confidence: 85%
See 4 more Smart Citations
“…The results of similar experiments by Zhang et al (2007) also showed evidence of reduced excitability due to subthreshold responses although it was not explicitly stated by the authors. True spike rate adaptation should only depend on the onset spike rate.…”
Section: Spike Rate Adaptation and Interacting Phenomenamentioning
confidence: 85%
“…5D-I of that article). In fact, all three experimental studies (Litvak et al 2001;Heffer 2010;Zhang et al 2007) showed that the normalized spike rate decrement (or spike reduction ratio) increased concomitantly with stimulus frequency. This indicates that accommodation is contributing to the spike rate decrement in parallel to spike rate adaptation.…”
Section: Spike Rate Adaptation and Interacting Phenomenamentioning
confidence: 96%
See 3 more Smart Citations